Content, Correlation, and Meaning of Categories ‘Legal Person’ and ‘Legal Personality’: General-Purpose Aspect - VOLYNETS, Vitalii V.; SICHEVLIUK, Volodymyr A.; KAMINSKA, Ilona V. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
At the present stage of its development, the general theory of law is aimed at achieving, as far as possible, a greater degree of practical use. Legal theorists seek to answer questions that are devoid of scholastic nature and derive from the practice of real legal relations. The performance of this task involves the movement of fundamental science, which is the general theory of state and law, on the path of ascending from the array of abstract reflections of legal reality, already formed by it, to obtaining its more specific theoretical reproductions. The purpose of this study is to present the correlation of categories such as ‘legal person’ and ‘legal personality’. The relevance of the study lies in the inability to gain new knowledge without the dialectical application of the framework of categories and concepts and methodology of the theory of law to the study of special (e.g., branch) and single (implemented at the individual level) legal phenomena in their relation to the general regularities of the functioning of the state and law. The research presents the content, correlation and meaning of these categories in the theory of law, and demonstrates their diversified use in Ukrainian legislation. The content of the category ‘subject of law’ covers those persons to whom the rights, duties and responsibilities, which are enshrined in the rules of objective law, are addressed. The category of ‘legal personality’ emphasizes the key role of objective law in constituting legal personality.